Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1016/j.lfs.2014.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Using high resolution imaging to determine trafficking of corticotropin-releasing factor receptors in noradrenergic neurons of the rat locus coeruleus

Abstract: Trafficking of G protein-coupled receptors (GPCRs) is a critical determinant of cellular sensitivity of neurons. To understand how endogenous or exogenous ligands impact cell surface expression of GPCRs, it is essential to employ approaches that achieve superior anatomical resolution at the synaptic level. In situations in which light and fluorescence microscopy techniques may provide only limited resolution, electron microscopy provides enhanced subcellular precision. Dual labeling immunohistochemistry employ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 109 publications
(176 reference statements)
0
14
0
Order By: Relevance
“…Additionally, while we found no changes in CRF receptor mRNA in the VTA, binge-induced reductions of CRF-1R protein was significance. It has been reported that increases in CRF signaling promote the internalization and recycling of the CRF-1R (34-37), and thus the reduction in protein expression seen here likely reflects a compensatory response to counter increased CRF signaling…”
Section: Discussionmentioning
confidence: 71%
“…Additionally, while we found no changes in CRF receptor mRNA in the VTA, binge-induced reductions of CRF-1R protein was significance. It has been reported that increases in CRF signaling promote the internalization and recycling of the CRF-1R (34-37), and thus the reduction in protein expression seen here likely reflects a compensatory response to counter increased CRF signaling…”
Section: Discussionmentioning
confidence: 71%
“…Adapted from Krishnan et al, [14] NE Mechanisms of Resilience Emerging evidence implicates the LC-NE system in stress resilience [67][68][69]. It is well known that the LC-NE nucleus responds to stress by Bpriming^neurons throughout the brain [68,[70][71][72][73][74][75][76]. For instance, in response to acute stress, the LC-NE system shifts the brain into a rapid defense-mechanism state [77].…”
Section: Kcnq Potassium Channels As Novel Drug Targetsmentioning
confidence: 99%
“…Neuroanatomical evidence indicates that noradrenergic system in the brain arise from the cell bodies in the locus coeruleus and project to different cerebral regions and to the spinal cord (Cooper et al, 2002). Moreover, there is a complex interaction between norepinephrine (NE) and corticotrophin releasing factor (CRF), a neuropeptide strongly associated with central autonomic and stress activity, receptors within the locus coeruleus (Reyes, Bangasser, Valentino, & Van Bockstaele, 2014). In addition to major projections to the frontal cortex, (NE) neurons project to the limbic system (Flavin & Winder, 2013), including amygdala, bed nucleus of the stria terminalis, hippocampus, and hypothalamus where it is implicated in addiction (Becker, 2012; Koob, 2013; Sofuoglu, Rosenheck, Petrakis, 2014; See also Al’ Absi, 2007), anxiety (Geiger, Neufang, Stein, & Domschke, 2014), attention (Geiger et al, 2014; Hegerl & Hensch, 2014), cognition (Chandler, Waterhouse, & Gao, 2014), memory, mood (Gold, 2015), pain (Elman, Borsook, & Volkow, 2013; Strobel, Hunt, Sullivan, Sun, & Sah, 2014), post-traumatic stress disorder (PTSD, Sofuoglu et al, 2014; Wimalawansa, 2014), sleep (Zeitzer, 2013), suicide (Elman et al, 2013), and associated physiological processes (Klimek, Rajkowska, Luker, Dilley, et al, 1999; Moret & Briley, 2011).…”
Section: Some Neurochemical Neuropharmacological As Well As Neurmentioning
confidence: 99%